2019
DOI: 10.1589/jpts.31.498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of foot kinetics and kinematics during gait initiation between young and elderly participants

Abstract: [Purpose] To investigate the differences in foot kinetics during gait initiation between young and elderly participants using a modified multi-segment foot model. [Participants and Methods] Twelve young (23.3 ± 2.4 years) and 12 elderly participants (73.3 ± 3.9 years) were included in this study. Gait initiation was measured using a three-dimensional motion analysis system. We calculated the kinetic and kinematic values using our modified multi-segment foot model and compared those values with the values calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The transit time was longer by 30% in subjects over 70 y/o, which lead to prolonged DST, S1, and S2. In previous studies, the authors analyzed various gait parameters in older adults, mostly gait speed, step length, and stride length, and rarely double-support time [ 22 , 23 ]. Some authors [ 24 ] observed that adults aged 65–79 y/o present a 20% slower gait speed relative to young adults (20–25 y/o).…”
Section: Discussionmentioning
confidence: 99%
“…The transit time was longer by 30% in subjects over 70 y/o, which lead to prolonged DST, S1, and S2. In previous studies, the authors analyzed various gait parameters in older adults, mostly gait speed, step length, and stride length, and rarely double-support time [ 22 , 23 ]. Some authors [ 24 ] observed that adults aged 65–79 y/o present a 20% slower gait speed relative to young adults (20–25 y/o).…”
Section: Discussionmentioning
confidence: 99%
“…The transit time was longer by 30% in subjects over 70 y/o, which lead to prolonged DST, S1, and S2. In previous studies, the authors analyzed various gait parameters in the elderly, mostly gait speed, step length, and stride length, and rarely double-support time [10,11]. Some authors [12] observed that adults aged 65-79 y/o present a 20% slower gait speed relative to young adults (20-25 y/o).…”
Section: Discussionmentioning
confidence: 99%
“…Whole body movements were recorded using a three-dimensional motion analysis system (Vicon Nexus; Oxford Metrics, London, UK) with 12 infrared cameras with a sampling frequency of 100 Hz. Markers were applied to the whole body with reference to Vicon and previous studies [ 33 ]. Markers were applied according to the Gait Full-body Model plug-in in Vicon ( https://www.vicon.com/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Markers were applied according to the Gait Full-body Model plug-in in Vicon ( https://www.vicon.com/ ). Additional markers were used for detailed analysis of the feet [ 33 ]. Ground reaction forces were recorded on four force plates (Kisler Japan, Tokyo, Japan) with a sampling frequency of 1000 Hz.…”
Section: Methodsmentioning
confidence: 99%